INNOVATIVE PRACTICE OF SOCIO-EDUCATIONAL WORK IN PROBATION SERVICE IN UKRAINE - Lisovets Оleg (Social work and education, 2018)
The implementation of the probation service in Ukraine has considerably activated the questions of working out the new approaches to the social work with different categories of the persons having the problems with the law. In this article we try to examine the essence and peculiarities of socio-educational work with the convicted persons as innovative practice for probation service and the efficiency of its implementation at present stage in Ukraine. The probation service we consider as the subject of the social work, because it includes the specific directions and functions, which are directed to the decision of the client’s social problems, incl. it provides the socio-educational work implementation for the purpose of the convicted persons’ correction. Having analyzed the experience of the probation service socio-educational work we can separate such main directions: consultative help, assistance in the job placement, attraction for study, participation in the breeding actions and socio-useful activity. We’ve formulated and characterized the basic possible problems and needs of the probation subject. With the help of diagnostic methodic we’ve analyzed the basic problems and needs of Nizhyn and regional probation service department clients and proranged according to the level of town criminology the dynamic factors of the risk. The definition the client’s problems and needs is an outgoing and necessary stage of one of the basic and innovative technologies of the socio-educational work with the probation subjects – the technology of the case-management. And one of the new practices in the probation service work the implementation of the probation programs becomes. The program includes a series of measures aimed at correcting social behavior or its individual manifestations, forming socially favorable changes in the individual. The questions of the probation service personnel and methodical support in Ukraine need further scientific research, the interaction of the probation institutions with the other social institutions for the clients’ problems decision.